Folding and aggregation energy landscapes of tethered RRM domains of human TDP-43 are coupled via a metastable molten globule-like oligomer - Pillai, Meenakshi; Jha, Santosh Kumar (Biochemistry, 2019)
Stress-induced misfolding and intraneuronal aggregation of the highly conserved nucleic acid binding protein TDP-43 (transactive response DNA binding protein 43 kDa) and its fragments have been implicated in amyotrophic lateral sclerosis and several other neurodegenerative diseases. However, the physicochemical mechanism of its misfolding from the functional folded state is poorly understood. TDP-43 is a four-domain protein and performs the essential nucleic acid binding function with the help of its two tandem RNA recognition motif domains naturally tethered by a linker (called here the tethered RRM domain of TDP-43 or TDP-43(tRRM)). Here, we show that the monomeric native form of TDP-43(tRRM) remains in a pH-dependent and reversible thermodynamic equilibrium with a protonated, nanosized, 40-merit form (the A form). Under the stress-like low-pH condition, the A form becomes predominantly populated. In the A form, protein molecules have restricted dynamics of surface side-chain residues but native-like secondary structure. This self-assembled form possesses a loosely packed core in which the intrinsically disordered and aggregation-prone regions are in the proximity. The A form is metastable and swiftly aggregates into a highly stable amyloid-like protofibrillar form (beta form) mediated by the disorder-to-order transition of intrinsically disordered regions upon small environmental perturbations. Interestingly, the A form and the beta form are not formed when TDP-43(tRRM) is bound to DNA, indicating that the nucleic acid binding regions of the protein participate in their formation. Our results reveal how the energy landscapes of folding and aggregation of TDP-43(tRRM) are coupled by a metastable molten-globule like oligomeric form and modulated by stress-like conditions.

Early metastable assembly during the stress-induced formation of worm-like amyloid fibrils of nucleic acid binding domains of TDP-43 - Pillai, Meenakshi; Jha, Santosh Kumar (Biochemistry, 2020)
TDP-43 protein travels between the cytosol and the nucleus to perform its nucleic acid binding functions through its two tandem RNA recognition motif domains (TDP-43(tRRM)). When exposed to various environmental stresses, it forms abnormal aggregates in the cytosol of neurons, which are the hallmarks of amyotrophic lateral sclerosis and other TDP-43 proteinopathies. However, the nature of early structural changes upon stress sensing and the consequent steps during the course of aggregation are not well understood. In this study, we show that under low-pH conditions, mimicking starvation stress, TDP-43(tRRm) undergoes a conformational opening reaction linked to the protonation of buried ionizable residues and grows into a metastable oligomeric assembly (called the ``low-pH form'' or the ``L form''). In the L form, the protein molecules have disrupted tertiary structure, solvent-exposed hydrophobic patches, and mobile side chains but the native-like secondary structure remains intact. The L form structure is held by weak interactions and has a steep dependence on ionic strength. In the presence of as little as 15 mM KCl, it fully misfolds and further oligomerizes to form a beta-sheet rich ``beta form'' in at least two distinct steps. The beta form has an ordered, stable structure that resembles worm-like amyloid fibrils. The unstructured regions of the protein gain structure during L (sic) beta conversion. Our results suggest that TDP-43(tRRm) could function as a stress sensor and support a recent model in which stress sensing during neurodegeneration occurs by assembly of proteins into metastable assemblies that are precursors to the solid aggregates.

Electrostatic modulation of intramolecular and intermolecular interactions during the formation of an amyloid-like assembly - Pillai, Meenakshi; Das, Atanu; Jha, Santosh Kumar (Biochemistry, 2023)
The mechanism of protein aggregation can be broadly viewedas ashift from the native-state stabilizing intramolecular to the aggregated-phasesustaining intermolecular interactions. Understanding the role ofelectrostatic forces on the extent of modulation of this switch hasrecently evolved as a topic of monumental significance as proteinaggregation has lately been connected to charge modifications of anaging proteome. To decipher the distinctive role of electrostaticforces on the extremely complicated phase separation landscape, weopted for a combined in vitro-in silico approach to ascertainthe structure-dynamics-stability-aggregabilityrelationship of the functional tandem RRM domains of the ALS-relatedprotein TDP-43 (TDP-43(tRRM)), under a bivariate solutioncondition in terms of pH and salt concentration. Under acidic pH conditions,the native TDP-43(tRRM) protein creates an aggregation-proneentropically favorable partially unfolded conformational landscapedue to enthalpic destabilization caused by the protonation of theburied ionizable residues and consequent overwhelming fluctuationsof selective segments of the sequence leading to anti-correlated movementsof the two domains of the protein. The evolved fluffy ensemble witha comparatively exposed backbone then easily interacts with incomingprotein molecules in the presence of salt via typical amyloid-aggregate-likeintermolecular backbone hydrogen bonds with a considerable contributionoriginating from the dispersion forces. Subsequent exposure to excesssalt at low pH conditions expedites the aggregation process via anelectrostatic screening mechanism where salt shows preferential bindingto the positively charged side chain. The applied target observable-specificapproach complementarity unveils the hidden information landscapeof an otherwise complex process with unquestionable conviction.

Multistep molecular mechanism of amyloid-like aggregation of nucleic acid-binding domain of TDP-43 - Pillai, Meenakshi; Jha, Santosh Kumar (Proteins- Structure Function and Bioinformatics, 2023)
TDP-43 protein is associated with many neurodegenerative diseases and has been shown to adopt various oligomeric and fibrillar states. However, a detailed kinetic understanding of the structural transformation of the native form of the protein to the fibrillar state is missing. In this study, we delineate the temporal sequence of structural events during the amyloid-like assembly of the functional nucleic acid-binding domain of TDP-43. We kinetically mapped the aggregation process using multiple probes such as tryptophan and thioflavin T (ThT) fluorescence, circular dichroism (CD), and dynamic light scattering (DLS) targeting different structural events. Our data reveal that aggregation occurs in four distinct steps-very fast, fast, slow, and very slow. The ``very fast'' change results in partially unfolded forms that undergo conformational conversion, oligomerization and bind to ThT in the ``fast step'' to form higher order intermediates (HOI). The temporal sequence of the formation of ThT binding sites and conformational conversion depends upon the protein concentration. The HOI further undergoes structural rearrangement to form protofibrils in the ``slow'' step, which, consequently, assembles in the ``very slow'' step to form an amyloid-like assembly. The spectroscopic properties of the amyloid-like assembly across the protein concentration remain similar. Additionally, we observe no lag phase across protein concentration for all the probes studied, suggesting that the aggregation process follows a linear polymerization reaction. Overall, our study demonstrates that the amyloid-like assembly forms in multiple steps, which is also supported by the temperature dependence of the kinetics.
Keywords: aggregation pathway; amyloid-like assembly; conformational conversion; kinetics; oligomers

Conformational enigma of TDP-43 misfolding in neurodegenerative disorders - Pillai, Meenakshi; Jha, Santosh Kumar (ACS OMEGA, 2024)
Keywords: DNA-BINDING PROTEIN; FRONTOTEMPORAL LOBAR DEGENERATION

Pathological mutations D169G and P112H electrostatically aggravate the amyloidogenicity of the functional domain of TDP-43 - Pillai, Meenakshi; Patil, Anjali D.; Das, Atanu; Jha, Santosh Kumar (ACS Chemical Neuroscience, 2024)
Aggregation of TDP-43 is linked to the pathogenesis of many neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS). Notably, electrostatic point mutations such as D169G and P112H, located within the highly conserved functional tandem RNA recognition motif (RRM) domains of the TDP-43 protein (TDP-43tRRM), have been identified in diseased patients as well. In this study, we address how the electrostatic mutations alter both the native state stability and aggregation propensity of TDP-43tRRM. The mutants D169G and P112H show increased chemical stability compared to the TDP-43tRRM at physiological pH. However, at low pH, both the mutants undergo a conformational change to form amyloid-like fibrils, though with variable rates-the P112H mutant being substantially faster than the other two sequences (TDP-43tRRM and D169G mutant) showing comparable rates. Moreover, among the three sequences, only the P112H mutant undergoes a strong ionic strength-dependent aggregability trend. These observations signify the substantial contribution of the excess charge of the P112H mutant to its unique aggregation process. Complementary simulated observables with atomistic resolution assign the experimentally observed sequence-, pH-, and ionic strength-dependent aggregability pattern to the degree of thermal lability of the mutation site-containing RRM1 domain and its extent of dynamical anticorrelation with the RRM2 domain whose combination eventually dictate the extent of generation of aggregation-prone partially unfolded conformational ensembles. Our choice of a specific charge-modulated pathogenic mutation-based experiment-simulation-combination approach unravels the otherwise hidden residue-wise contribution to the individual steps of this extremely complicated multistep aggregation process.
Keywords: amyloid fibrils; conformational changes; disease mutations; electrostatics; Protein aggregation; stability